Attachment-Focused Therapeutic Intervention to Developmental Trauma in School Environment - Şeyda Sofuoğlu; İpek Güzide Pur-Karabulut (Anı Publishing, 2019)
The aim of the research is to discover the attachment pattern of adolescents with the risk of dropping out of school and their mothers by taking into account of these adolescents' childhood. In accordance with this purpose, a qualitative research is conducted by interviewing two high school students, 16 and 18 years old, and two other high school students' mothers. Thematic analysis method was implemented to the data collected by personal information form, interview content reports, survey reports and supervision reports. MAXQDA which is a software package for qualitative and mixed methods research was utilized during qualitative analysis. It was determined that all participants were exposed to neglect and abuse which started in early childhood and proceeded into adolescence period. It was observed that another environment participants were exposed to abuse was school environment. In addition, it was seen that all participants have difficulty in regulating their emotions. We argue that participants who have traumatic attachment and insecure attachment patterns, are the victims of developmental trauma. The fact that participants have difficulty in regulating emotions may be explained via insecure attachment pattern and developmental trauma. It was determined that the attachment-oriented therapeutic intervention that is implemented in the research has positiveimpact on healing thanks to the participants' statements.